Cavity-enhanced magnetometer with a spinor Bose–Einstein condensate. (8th April 2021) - Gietka, Karol; Mivehvar, Farokh; Busch, Thomas
Abstract: We propose a novel type of composite light–matter magnetometer based on a transversely driven multi-component Bose–Einstein condensate coupled to two distinct electromagnetic modes of a linear cavity. Above the critical pump strength, the change of the population imbalance of the condensate caused by an external magnetic field entails the change of relative photon number of the two cavity modes. Monitoring the cavity output fields thus allows for nondestructive measurement of the magnetic field in real time and we show that the sensitivity of the proposed magnetometer exhibits Heisenberg-like scaling with respect to the atom number. For state-of-the-art experimental parameters, we calculate the lower bound on the sensitivity of such a system to be of the order of fT ( H z ) − 1 –pT ( H z ) − 1 for a condensate of 10 4 atoms with coherence times on the order of several ms.